A cloud model-based multi-level fuzzy comprehensive evaluation approach for financing credit of scientific & technological small-medium enterprises. Issue 1 (1st February 2017) - Li, Jie; Zhang, Qiuwen; Yan, Fei; Zhong, Ming
Abstract : Financing difficulty is one of the most important bottlenecks for the further development of scientific and technological small–medium enterprises (STSMEs). The key to solve this problem lies in reducing the information asymmetry between the two sides of the capital supply and the demand, which may be relieved effectively by establishing a standardized evaluation index system and a corresponding evaluation model of financing credit for STSMEs. In this paper, a new evaluation index system for financing credit of STSMEs in both macro and micro aspects is constructed, and the cloud model is introduced to improve the analytic hierarchy process (AHP) and fuzzy comprehensive evaluation method so that a multi-level fuzzy comprehensive evaluation approach of financing credit for STSMEs is improved by the cloud model. Finally, a case study of thirty enterprises from NEW OTCBB or capital market in China is used to illustrate the proposed method. It is shown that the cloud model-based multi-level fuzzy comprehensive evaluation approach can reduce randomness and uncertainty in the determination process of index weight and membership degree, and therefore enhance the robustness of the evaluation.